Career readiness of graduating BSA students of De La Salle University - Manila in industry 4.0 - Aman, Micah Ela A. (Animo Repository, 2023)
Industry 4.0, with the emergence of new technologies, brings significant disruptions to the accounting industry, particularly to the skills and competencies expected from graduating students. This study employed a causal research design to evaluate the career readiness of graduating Bachelor of Science in Accountancy (BSA) students from De La Salle University-Manila for employment in an Industry 4.0 setting. The research also aimed to assess their levels of technological self-efficacy and technology acceptance. Participants responded to a three-part online questionnaire, and the data were analyzed using descriptive statistics, linear regression, ANOVA, and moderated regression. The results indicated that graduating BSA students exhibit moderate preparedness for employment in the context of Industry 4.0. Although they are aware of the significant impact and rapid advancements brought about by Industry 4.0, the students lack strong foundations and competencies in both existing and emerging technologies. The findings of this study have implications for key stakeholders, underlining the importance of students acquiring relevant skills to ensure success in their professional pursuits. Key Words: Industry 4.0; Career readiness; Technological self-efficacy; Technology acceptance; Skills development